(untitled) (Global Journal of Science Frontier Research, 2020)
The study area Mukuru is in the eastern part of Boki LGA in Cross River State. It is a high grade granulites terrain, others rock types identified are charnockitic, migmatitic and less of granitic and doleritic rocks. The extracted lineaments from the satellite imagery are in a zone of charnockitic rocks belt highlands and migmatites lowlands. They appear as lines or edges and the colour differences help to identify them on straight rock boundaries, valleys and drainage channels. The total number of 265 altitudes of planar and linear features were mapped. The accuracy of the lineaments depends on ground-truth of the results of lineament survey. The charnockites have caves which can accommodate ten to two hundred people. Rockfalls or rockslides geohazards mapping and analysis can provide valuable information to ease the catastrophic loss, reduce loss of lives and properties, and also provide guidelines for a sustainable planning and development. All the areas surrounded by highlands are potential geohazard zone, this has been recorded at Bumaji, Ofambe and Buanchor, they needs monitoring and evaluation.